Study on the effect of different nutrients on the growth of a Trichoderma aureoviride mutant - CHEN Jian-ai; WANG Wei-ming (浙江大学学报. 农业与生命科学版)
Trichoderma aureoviride mutant T1010 was cultured in media containing different nutrients. Statistics showed significant differences and the results described below: The C/N tested were 3:1, 6:1, 12:1,24:1,48:1. The best C/N was 24:1. The amount of spores was 4.0 × 109 cfu/plate. The best carbon source among glucose, sucrose, maltose, lactose, cellulose and starch was the last one. With a starch-containing medium, T1010 produced 5.3 × 109 cfu/plate. The asparagine was the best nitrogen source. T1010 absorbed it easily and produced 9.6× 109 cfu/plate. K, Mg, P, S, Fe were important to support T1010 growth and sporulation. In the absence of K, P, and Fe, Trichoderma grew poorly, while Mg didn't seem to help Trichoderma colony development. A little amount of vitamins all wed T1010 to grow better. This data allowed us to improve the cultivation of Trichoderma at industrial level.